Long term trends and dynamics of dissolved organic carbon (DOC) in a subtropical Reservoir basin - Chow M.F.; Lai C.-C.; Kuo H.-Y.; Lin C.-H.; Chen T.-Y.; Shiah F.-K. (MDPI AG, 2023)
Acidification; Atmospheric chemistry; Atmospheric temperature; Deposition; Dissolution; Meteorological problems; Organic carbon; Rivers; Stream flow; Atmospheric depositions; Dissolved organic carbon; Hydrological factors; Long-term trend; Positive correlations; Seasonal variability; Stream; Streamwater chemistry; Reservoirs (water); atmospheric deposition; concentration (composition); dissolved organic carbon; environmental factor; ionic composition; long-term change; oligotrophic environment; reservoir; streamwater; subtropical region; temperature effect; trend analysis; Feitsui Reservoir; Taiwan